2014
DOI: 10.3389/fpls.2014.00463
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium-mediated genetic transformation of yam (Dioscorea rotundata): an important tool for functional study of genes and crop improvement

Abstract: Although genetic transformation of clonally propagated crops has been widely studied as a tool for crop improvement and as a vital part of the development of functional genomics resources, there has been no report of any existing Agrobacterium-mediated transformation of yam (Dioscorea spp.) with evidence of stable integration of T-DNA. Yam is an important crop in the tropics and subtropics providing food security and income to over 300 million people. However, yam production remains constrained by increasing l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 78 publications
1
55
0
1
Order By: Relevance
“…All these conditions of different parameters would help us in developing a congenial high throughput method of Agrobacterium mediated genetic transformation in maize. Similar studies were done in Rice (Ignacimuthu and Raveendar, 2011;Sahoo and Tuteja, 2012) and Yam (Nyaboga et al, 2014). This study will help in maize genetic engineering for agronomically demand traits into recalcitrant maize genotypes.…”
Section: Recovery Of Fertile Transgenic Plants Throughsupporting
confidence: 65%
See 1 more Smart Citation
“…All these conditions of different parameters would help us in developing a congenial high throughput method of Agrobacterium mediated genetic transformation in maize. Similar studies were done in Rice (Ignacimuthu and Raveendar, 2011;Sahoo and Tuteja, 2012) and Yam (Nyaboga et al, 2014). This study will help in maize genetic engineering for agronomically demand traits into recalcitrant maize genotypes.…”
Section: Recovery Of Fertile Transgenic Plants Throughsupporting
confidence: 65%
“…Thorough optimizing and tuning those parameters with different genotypes are necessary for getting high frequencies of transformation (Cao et al, 2014), where different genotypes were used by considering the different parameters and achieved 2% transformation frequency in maize using multiple shoots developed from the coleoptilar nodal explant. In contrary to this, in present study transformation studies have been done by using callus cultures developed from the same explant and frequencies were assessed by using hygromycin selection frequency (Nyaboga et al, 2014). In the present study, it was concluded that the parameters viz., one day pre-conditioning of explants, 0.8 optical density of bacterial culture in plain MS liquid infection medium having 5.8 pH along with 200 µM acetosyrengone, 15 minutes infection time for the explants after treating with 0.1% Macerozyme, application of vacuum infiltration for 10 minutes, three days of co-cultivation period, play a vital role in maize transgenic development from coleoptilar nodal explant.…”
Section: Recovery Of Fertile Transgenic Plants Throughmentioning
confidence: 72%
“…The accession was maintained in vitro and multiplied through nodal cuttings on yam basic medium (YBM) containing Murashige and Skoog medium (MS) salts and vitamins, 0.05 mg/l 6-Benzylaminopurine (BAP), 0.02 mg/l Naphthaleneacetic acid (NAA), 25 mg/l Ascorbic acid, 30 g/l sucrose, and 2.4 g/l gelrite, as described by Nyaboga et al (2014) (Fig. 1a).…”
Section: Plant Materialsmentioning
confidence: 99%
“…The crop has great economic and social significance in sub-Saharan Africa (Ile et al 2006) where more than 95 % of the world's yam is produced (FAO 2013). Of the 600 known Dioscorea species only 10 of the 90 edible species are consistently cultivated for food consumption (Nyaboga et al 2014) and the Dioscorea rotundata species complex is among the most cultivated, especially in West Africa (FAO 2013). Besides its importance as a staple food, yam is also a source of income for people, particularly in the coastal region of West Africa (Asiedu and Sartie 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation